A Digital Image Correlation Analysis of Strain Generated by 3-Unit Implant-Supported Fixed Dental Prosthesis: An In Vitro Study. Issue 4 (August 2017) - Peixoto, Raniel F.; Macedo, Ana P.; Martinelli, Janisse; Faria, Adriana C. Lapria; Tiossi, Rodrigo; Ribeiro, Ricardo F.; de Mattos, Maria da G. C.
Abstract : Objective: To evaluate the influence of different veneering materials (porcelain and resin) and implants (short and conventional) in the strain distribution of implant-supported splinted fixed partial dentures (FPDs) using digital image correlation (DIC). Material and Methods: Four polyurethane models were fabricated with resin replicas (first premolar) and short and/or conventional implants replacing the second premolar and first and second molars, according to the following configurations: G1, 2 conventional (second premolar and first molar) and 1 short (second molar) implant; G2, 1 conventional (second premolar) and 2 short (first and second molar) implants; G3, 3 short implants; G4, 3 conventional implants. Porcelain- and resin-veneered splinted FPDs were screwed to the implant abutments. The DIC system was used to calculate strains during application of occlusal load (250 N). Results: Porcelain- and resin-veneered showed similar strain distribution for all groups ( P > 0.05). Concentration of compressive strains was higher in G3P and G3R with maximum compressive strains of −1271.50 and −1026.88 μs, respectively. G4 transferred the best strain distribution (porcelain, −275.14 μs; resin, −254.44 μs), followed by G2 (porcelain, −306.79 μs; resin, −310.63 μs). Conclusion: The veneering material used did not influence the strain distribution. In addition, conventional implants generate less strain concentration, although the combination of 2 short and 1 conventional implant seems to be a viable plan.